GLYCEMIC CONTROL AND COGNITIVE FUNCTION AFTER 50 YEARS OF TYPE 1 DIABETES - Yu, Marc Gregory; Shah, Hetal; Wolfson, Emily; Bahnam, Vanessa; King, George (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION While cognitive dysfunction is well-studied in type 2 diabetes (T2D), research in type 1 diabetes (T1D) remains scant. In the Medalist Study at Joslin Diabetes Center (“Medalists”), individuals with ≥50 years of TID were previously shown to have impaired cognitive function, similar to those with T2D. However, the association of glycemic control with cognitive impairment has not been investigated. METHODOLOGY Medalists with no pre-existing CNS conditions or intake of medications affecting cognitive function were recruited for this cross-sectional study. They underwent the following tests: The Rey Auditory Verbal Learning Test assessing both immediate and delayed memory; the Wechsler Memory Scale III assessing working memory; the Delis-Kaplan Executive Function System assessing executive function; and the Grooved Pegboard Test assessing motor skills for both the dominant (DH) and non-dominant (NDH) hand. The association of glycemic control with cognitive function was evaluated using linear regression. RESULTS In the overall cohort (n=110), HbA1c was significantly associated with worse executive function even after adjusting for covariates (p=0.01). Medalists in the highest HbA1c tertile (7.5-9.2%) also trended (p=0.08) towards worse executive function as compared to Medalists in the middle (6.8-7.4%) and lowest (5.0-6.7%) tertiles. Furthermore, HbA1c was significantly associated with worse DH motor skills (p=0.047), and trended (p=0.09) towards association with worse immediate memory, among Medalists in the lowest tertile of disease duration (50-51 years). CONCLUSION Worse glycemic control was associated with cognitive dysfunction in the Medalists. Given the increasing life expectancy of individuals with T1D, a multidisciplinary approach is recommended to promote strategies that prevent cognitive decline.